Mustard seed (Sinapis Alba Linn) attenuates imiquimod‐induced psoriasiform inflammation of BALB/c mice. Issue 7 (19th May 2013) - Yang, Runping; Zhou, Qiang; Wen, Chunmiao; Hu, Jian; Li, Hengjin; Zhao, Ming; Zhao, Hua
Abstract Psoriasis is a chronic inflammatory autoimmune disease with undefined etiology. All present treatments are symptomatic. The unsatisfactory outcome in the treatment of psoriasis is partially due to the poor compliance to the present therapies with more or less side‐effects. As is known, drug homologous food is a popular intervention of some chronic diseases in Chinese traditional medicine. Mustard seed, consumed largely as a spice and a medicine in China, has recently been found to possess the bioactivities of anti‐oxidation, anti‐inflammation and anticancer. Therefore, it was supposed that mustard seed may have effects on psoriasis, and it was preliminarily validated using a BALB/c mouse model of psoriasiform inflammation induced by the topical application of imiquimod cream (Aldara) for 6 days consecutively. It was found that the forage containing 5% mustard seed obviously attenuated imiquimod‐induced psoriasiform inflammation, but did not clear it completely, accompanied by reduced infiltrations of T cells, plasmacytoid dendritic cells (pDC) and macrophages in lesional skin; reduced percentages of pDC and macrophages in the composition of immunocytes of spleens; reduced content of lesion nuclear factor‐κB p65, plasma malondialdehyde, lesion inducible nitric oxide synthase, interferon‐α, interleukin (IL)‐17 and IL‐22 at mRNA and protein levels; increased activities of superoxide dismutase, catalase and glutathione peroxidase; and increased percentage of CD4+ T cells and increased ratio of CD4+/CD8+ T cells in the composition of immunocytes of spleen. These results presented herein provide a basis for mustard seed to be used as a promising intervention for psoriasis in the future.